2022
DOI: 10.1080/09603123.2022.2065249
|View full text |Cite
|
Sign up to set email alerts
|

Climate and visitors as the influencing factors of dengue fever in Badung District of Bali, Indonesia

Abstract: doi: medRxiv preprint NOTE: This preprint reports new research that has not been certified by peer review and should not be used to guide clinical practice.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…These include failure to control Aedes mosquito populations, uncontrolled urbanization, unprecedented population growth, and climate variations. 26,27 This present study also informs that the preventive action most preferred by participants is periodically emptying or drying out containers that retain water around the house such as bathtubs, jugs, water towers, drums and other water reservoirs (76.5%), and applying larvicide treatment and other mosquito repellents (70.8%). The application of mosquito-proof nets will not be effective in preventing Aedes mosquito bite incidents because most mosquito-proof nets are only used at night.…”
Section: Discussionmentioning
confidence: 58%
“…These include failure to control Aedes mosquito populations, uncontrolled urbanization, unprecedented population growth, and climate variations. 26,27 This present study also informs that the preventive action most preferred by participants is periodically emptying or drying out containers that retain water around the house such as bathtubs, jugs, water towers, drums and other water reservoirs (76.5%), and applying larvicide treatment and other mosquito repellents (70.8%). The application of mosquito-proof nets will not be effective in preventing Aedes mosquito bite incidents because most mosquito-proof nets are only used at night.…”
Section: Discussionmentioning
confidence: 58%
“…Some of the factors that affect the spread of dengue fever include climate change (3), global, economic growth, population density (4), clean water availability and community behavior (5). One of the key factors of eradicating dengue fever is community behavior (6).…”
Section: The Government-regulated Denguementioning
confidence: 99%
“…A study done in Indonesia during the period of 2013 -2019 has shown that there 0.0005 increase for 1mm precipitation (2 months lag) (Maulana et al, 2021).…”
Section: Impact Of Precipitation On Denguementioning
confidence: 99%
“…According to a study in Indonesia during 2013 -2019 period, the number of dengue cases has increased by 0.0143 for 1% humidity (Maulana et al, 2021). A study conducted in Indonesia during the period of 2003revealed that the dengue incidence will decrease with humidity of 70 to 75% and it will increase with humidity of to 87%.…”
Section: 54392/ajir2314mentioning
confidence: 99%